FTO rs17817449 Variant Increases the Risk of Severe Obesity in a Brazilian Cohort: A Case-Control Study - Salum KCR; Assis ISS; Kopke ÚA; Palhinha L; Abreu GM; Gouvêa LW; Teixeira MR; Mattos FCC; Nogueira Neto JF; Felício RFM; Rosado EL; Zembrzuski VM; et al. (Diabetes, Metabolic Syndrome and Obesity)
Kaio Cezar Rodrigues Salum,1,2 Izadora Sthephanie da Silva Assis,1,2 Úrsula de Almeida Kopke,3 Lohanna Palhinha,4 Gabriella de Medeiros Abreu,2,5 Laura Wendling Gouvêa,1,2 Myrela Ribeiro Teixeira,2,6,7 Fernanda Cristina C Mattos,5 José Firmino Nogueira Neto,8 Rafaela de Freitas Martins Felício,9,10 Eliane Lopes Rosado,5 Verônica Marques Zembrzuski,2 Mario Campos Junior,2 Clarissa Menezes Maya-Monteiro,4 Pedro Hernán Cabello,2 João Regis Ivar Carneiro,1 Patrícia Torres Bozza,4 Fabiana Barzotto Kohlrausch,6 Ana Carolina Proença da Fonseca2,4,11 1Medical Clinic Department, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil; 2Human Genetics Laboratory, Oswaldo Cruz Institute, Rio de Janeiro, Brazil; 3Chester Medical School, University of Chester, Chester, UK; 4Laboratory of Immunopharmacology, Oswaldo Cruz Institute, Rio de Janeiro, Brazil; 5Institute of Nutrition Josué de Castro, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil; 6Human Genetics Laboratory, Institute of Biology, Federal Fluminense University Niterói, Rio de Janeiro, Brazil; 7Postgraduate in Sciences and Biotechnology, Fluminense Federal University Niterói, Rio de Janeiro, Brazil; 8Department of Pathology and Laboratory, Rio de Janeiro State University, Rio de Janeiro, Brazil; 9Birth Defect Epidemiology laboratory, Oswaldo Cruz Institute, Rio de Janeiro, Brazil; 10Health Care Network for Congenital Anomalies of the Central Nervous System, Instituto Oswaldo Cruz, Rio de Janeiro, Brazil; 11Genetics Laboratory, Grande Rio University, Rio de Janeiro, BrazilCorrespondence: Ana Carolina Proença da Fonseca, Laboratory of Immunopharmacology, Oswaldo Cruz Institute, Oswaldo Cruz Foundation (Fiocruz), 4365 Brasil Avenue, 108 Building – Office 44, Rio de Janeiro, 21040-360, Brazil, Tel +55(21)38658192, Email ana.proenca@ioc.fiocruz.br Kaio Cezar Rodrigues Salum, Human Genetics Laboratory, Oswaldo Cruz Institute, Oswaldo Cruz Foundation (Fiocruz), 4365 Brasil Avenue, Leônidas Deane Building – Office 611/615, Rio de Janeiro, 21040-360, Brazil, Tel +55 21 38658213, Fax +55 21 38658239, Email kaio.salum@hotmail.comPurpose: Obesity is a complex disease caused by a combination of genetic, environmental, and epigenetic factors, and is associated with an increased risk of chronic diseases. The leptin-melanocortin pathway integrates peripheral signals about the body’s energy stores with a central neuronal circuit in the hypothalamus. This pathway has been extensively studied over the years, as genetic variations in genes related to it may play a crucial role in determining an individual’s susceptibility to obesity. Therefore, we analyzed the association between obesity and specific polymorphisms in leptin-melanocortin-related genes such as LEPR rs1137101, POMC rs1042571, LEP rs7799039, BDNF rs6265, FTO rs17817449, CART rs121909065, and NPY rs16147/rs5574.Patients and Methods: The study enrolled 501 participants from Rio de Janeiro, Brazil, with obesity class II or greater (BMI ≥ 35 kg/m2) and normal weight controls (18.5≤ BMI ≤ 24.9 kg/m2). We collected demographic, body composition, biochemical, and genotyping data by real-time PCR, and performed logistic and linear regression analyses to investigate the association of polymorphisms with severe obesity status and obesity-related quantitative parameters.Results: Individuals with severe obesity had significantly higher anthropometric measures, blood pressure, and biochemical levels. The FTO rs17817449 TT genotype was associated with a significantly higher risk of developing severe obesity, and distinct cytokine expression was observed across the FTO rs17817449 genotypes. The BDNF rs6265 dominant-model and NPY rs16147 CC genotypes were associated with triglyceride levels and childhood obesity, respectively. Finally, individuals with obesity were more likely to carry a greater number of risk alleles than those without obesity.Conclusion: Our study observed an important association between FTO rs17817449 polymorphism with obesity and obesity-related traits. Additionally, BDNF rs6265 dominant-model was associated with triglyceride serum levels, and NPY rs16147 may have a role in obesity onset.Keywords: FTO, polymorphisms, severe, leptin-melanocortin pathway, cytokines expression